ZmLBD5, a class‐II LBD gene, negatively regulates drought tolerance by impairing abscisic acid synthesis. (19th November 2022) - Feng, Xuanjun; Xiong, Jing; Zhang, Weixiao; Guan, Huarui; Zheng, Dan; Xiong, Hao; Jia, Li; Hu, Yue; Zhou, Hanmei; Wen, Ying; Zhang, Xuemei; Wu, Fengkai; et al.
SUMMARY: Lateral organ boundaries domain (LBD) proteins are plant‐specific transcription factors. Class‐I LBD genes have been widely demonstrated to play pivotal roles in organ development; however, knowledge on class‐II genes remains limited. Here, we report that ZmLBD5, a class‐II LBD gene, is involved in the regulation of maize ( Zea mays ) growth and the drought response by affecting gibberellin (GA) and abscisic acid (ABA) synthesis. ZmLBD5 is mainly involved in regulation of the TPS ‐ KS ‐ GA2ox gene module, which is comprised of key enzyme‐encoding genes involved in GA and ABA biosynthesis. ABA insufficiency increases stomatal density and aperture in overexpression plants and causes a drought‐sensitive phenotype by promoting water transpiration. Increased GA1 levels promotes seedling growth in overexpression plants. Accordingly, CRISPR/Cas9 knockout lbd5 seedlings are dwarf but drought‐tolerant. Moreover, lbd5 has a higher grain yield under drought stress conditions and shows no penalty in well‐watered conditions compared to the wild type. On the whole, ZmLBD5 is a negative regulator of maize drought tolerance, and it is a potentially useful target for drought resistance breeding. Significance Statement: Maize ( Zea mays ) ZmLBD5 is mainly associated with abscisic acid (ABA) and gibberellin (GA) synthesis by regulating the TPS‐KS‐GA2ox gene module, which is comprised of key enzyme‐encoding genes involved in GA and ABA biosynthesis. ZmLBD5 negatively regulates drought tolerance by repressing ABA synthesis and promoting stomatal development and opening; however, lbd5 mutants have higher grain yield under drought stress conditions and show no penalty in well‐watered conditions compared to the wild type.